Migration of the fungal pathogen Candida albicans across endothelial monolayers. - Zink, S (1996)
Migration of the fungal pathogen Candida albicans across the endothelial cell layer is considered a prerequisite for the invasion of multiple organs occurring in systemic candidiasis. We developed an experimental system in which C. albicans migrates from a luminal compartment across a monolayer of bovine aortic endothelial cells on a porous filter support to an abluminal compartment. In this system, a C. albicans wild-type strain (ATCC 10261) traverses the endothelial monolayer in a time-, glucose-, and cell concentration-dependent manner. A mutant derivative unable to grow and form hyphae (SGY-243) migrates at a reduced rate. Concomitant to transendothelial migration, the permeability of the endothelial monolayer for dextran diffusion markers is significantly increased. This increase in transendothelial exchange occurs before fungal cells are detectable in the abluminal compartment and is time, glucose, and cell concentration dependent. A mutant strain (hOG301) unable to interact with endothelial cells does not alter endothelial permeability. Thus, transendothelial migration of C. albicans is able to damage the barrier function of an endothelial monolayer. Our experimental system, which reflects key stages of transendothelial migration of C. albicans including adherence and passage across endothelial cells and the extracellular matrix, may be a useful model for comparisons of transendothelial migration characteristics of Candida strains.